Education for deaf students during the period of remote teaching in the covid-19 pandemic: a systematic review - Bandeira de Araújo, Katriny; de Lima Martins, Joseane (The ESPecialist, 2024)
The present study aimed to understand how educational institutions considered inclusive educational strategies for deaf students during remote teaching, given the social isolation caused by the COVID-19 pandemic. Regarding methodological procedures, it was carried out through a systematic review of the literature, with a qualitative approach. The results showed that schools adopted emergency measures to ensure that both students with disabilities – in this case, deafness – and students without disabilities had their rights respected and that their studies could continue, employing strategies to guarantee inclusion and accessibility for all . It was concluded that, for assistive technologies to be effective, it is crucial to invest in teacher training and ensure that they have access to the resources they need, truly implementing inclusive education.